Dust, Air, and Resistance: Multisensory Aesthetics Against Surveillance in Zia Haider Rahman’s In Light of What We Know - Filip, Loredana (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2026)
This article argues that literature offers distinctive ways of theorizing and resisting surveillance by foregrounding multisensory experience, materiality, and human–nonhuman entanglement. Within surveillance studies, resistance is often framed through visual or data-centric practices such as sousveillance, stealth, or counter-monitoring. By contrast, literary texts can disrupt surveillance at the level of perception itself. Focusing on Zia Haider Rahman’s In the Light of What We Know (2014), the article proposes a multisensory ecological aesthetics of resistance that shifts attention away from visibility and human agency toward atmosphere, ordinary matter, and nonhuman actors. Through recurring motifs of dust, air, and smell, the novel challenges colonial and anthropocentric regimes that seek to render environments and bodies fully legible. These sensory and material elements generate forms of opacity and relationality that exceed the visual and informational logics of surveillance. By reading literature as a multisensory medium that reconfigures how surveillance is perceived and contested, the article shows how literary analysis expands surveillance studies beyond visuality and toward an ecological understanding of resistance.